Liquisolid Technology: A State-of-the-Art Review on the Current State, Challenges, New and Emerging Technologies for Next Generation - Agiba, Ahmed M. (Current Drug Delivery, 2020)
Nowadays, the focus has been shifted to new technologies for improving drug solubility, permeability, and bioavailability, amid unprecedentedly increasing the number of newly discovered Active Pharmaceutical Ingredients (APIs), which are mostly categorized under Biopharmaceutical Classification System (BCS) as class-II and class IV. Traditional technologies and classical formulation strategies often fail to address most of the formulation problems associated with new APIs, particularly solubility and bioavailability. Therefore, exploring new and innovative technologies on an industrial scale is a prerequisite and requires modernization of manufacturing processes, as well as more advanced research and development. Liquisolid technology is a new, innovative industrial technology, particularly designed for either improving the release rates of poorly absorbed drugs or controlling their release pattern by achieving sustained-release profiles with zero-order release kinetics. Besides, it is a promising photoprotective system for photosensitive drugs and can further be used for modulating the drug microenvironmental pH. The next generation of liquisolid systems stems from a set of emerging technologies, such as liqui-pellet technology, which originates from combining liquisolid technology with pelletization technique, particularly extrusion-spheronization technique. This review article highlights the current state of liquisolid technology, ongoing challenges, characterization and applications, possible future prospects, the advent of new and emerging technologies, and the revolution of the next generation of liquisolid technology.
Keywords: possible future prospects